Conhecimento, atitudes e atividades de auto cuidado de indivíduos diabéticos tipo 2 nas estratégias saúde da família - Gonçalves, Nilce Elaine Xiol Morais (2014)
Objective: This study aimed to evaluate the knowledge, attitudes and self-care activities in patients with type 2 diabetes mellitus (DM2) in five units of the Family Health Strategy (FHS), a city in Minas Gerais, Brazil and also verify possible associations. Methodology: This was a descriptive cross-sectional study conducted from October 2013 to May 2014 was calculated representative population sample totaling 222 individuals. Data were collected through a script containing sociodemographic variables, time of diagnosis and treatment, in addition to the questionnaires Diabetes Knowledge Questionnaire (DKN-A); Diabetes Attitude Questionnaire (ATT-19); and the Summary of Diabetes Self-Care Activities Questionnaire (SDSCA). Results: The results showed that most participants 148 (66.7%) were female; aged 62 ± 12 years, and years DM duration of 11 ± 8 years. Only 10 (4,5%) of sample were using oral hypoglycemic agents and/or insulin. It was observed that the majority of individuals (66.7%) had scores greater than or equal to eight issues in the questionnaire DKN-A pointing to a satisfactory result. However, specific issues were observed with high error rate, especially as the dimensions hypoglycemia (70% errors), food substitutions (50% errors), dimension in the management of DM complication of some other disease and general principles of care of the disease (65% of errors). The questionnaire ATT-19, which measures attitudes to cope with the disease, results in 71.6% of scores, less than 70 indicating low readiness to face them. The knowledge and attitudes were not associated in the present study. In regard to self care (SDSCA) activities was observed that all individuals with DM taking medication daily however other aspects were negative: following the diet (mean 4 days / week), regular physical activity (mean 2 days / week), monitoring of blood glucose (mean 1.6 days / week), and foot care (mean 3.5 days / week). The dimensions of SDSCA, physical activity and following the diet for more than 5 days of the week were associated (chi -square equal to 7.8363 and p <0.01) as well as the diet was associated with a positive attitude towards the illness (chi-squared equals 2.4716 and p = 0.1159). Conclusion: Despite satisfactory knowledge by most individuals with DM, some points as food substitution, technical terms, guidelines for the management of insulin and medicines in clinical situations should be reinforced during visits of ESFs. The only activity of self care that all individuals with DM was observed following correctly is as medication, presenting negative and self care activities following a diet, physical activity, blood glucose monitoring, and foot care. Individuals with DM and positive attitude to face the DM follow diet for more than 5 days a week, which was also associated with frequent practice of physical activity. Keywords: Diabetes Mellitus; knowledge; Health Promotion; Attitude.